2019
DOI: 10.1016/j.ymgmr.2019.100465
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an iron-responsive subtype in two children diagnosed with relapsing-remitting multiple sclerosis using whole exome sequencing

Abstract: BackgroundMultiple sclerosis is a disorder related to demyelination of axons. Iron is an essential cofactor in myelin synthesis. Previously, we described two children (males of mixed ancestry) with relapsing-remitting multiple sclerosis (RRMS) where long-term remission was achieved by regular iron supplementation. A genetic defect in iron metabolism was postulated, suggesting that more advanced genetic studies could shed new light on disease pathophysiology related to iron.MethodsWhole exome sequencing (WES) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In pediatric MS with profound Fe deficit, patients stabilized after Fe supplementation. Authors speculated that oligodendroglial Fe deficiency leading to impaired ATP synthesis might have resulted in inefficient myelination and fragility of oligodendrocytes [374]. In line with this finding, mild association between decreasing transferrin saturation and increasing disability was shown in another study [375].…”
Section: Demyelinating Disorders and Neuroinflammationmentioning
confidence: 77%
“…In pediatric MS with profound Fe deficit, patients stabilized after Fe supplementation. Authors speculated that oligodendroglial Fe deficiency leading to impaired ATP synthesis might have resulted in inefficient myelination and fragility of oligodendrocytes [374]. In line with this finding, mild association between decreasing transferrin saturation and increasing disability was shown in another study [375].…”
Section: Demyelinating Disorders and Neuroinflammationmentioning
confidence: 77%
“…22 Sufficient iron and vitamin B12-folate methylation capacity is required by the mitochondria for this excessive energy generation. 6,23 If the oligodendrocytes experience energy blackouts they perish. 6,24 2.…”
Section: Discussionmentioning
confidence: 99%
“…In oligodendrocytes, the amount of iron is 20 times higher than in astrocytes, and since iron is a cofactor required for myelin synthesis, an excessive amount of intracellular iron will contribute to the development of ferroptosis ( Thorburne and Juurlink, 2002 ; Van Rensburg et al, 2019 ; She et al, 2021 ). Also, the investigators observed that oligodendrocyte precursor cells (OPCs) are more easily susceptible to the effects of extracellular free iron and intracellular cysteine depletion, which leads to an increase in lipid peroxidation, a blockage of oligodendrocyte differentiation, and cell death.…”
Section: Ferroptosis and Cells In Central Nervous Systemmentioning
confidence: 99%